Heart Rate Variability in Healthy Non-Concussed Youth Athletes: Exploring the Effect of Age, Sex, and Concussion-Like Symptoms - Paniccia, Melissa; Verweel, Lee; Thomas, Scott; Taha, Tim; Keightley, Michelle; Wilson, Katherine E.; Reed, Nick (Frontiers in Neurology, 2018)
Background: Heart rate variability (HRV) is a non-invasive neurophysiological measure of autonomic nervous system regulation emerging in concussion research. To date, most concussion studies have focused on the university-aged athlete with no research examining healthy active youths. Corroborating change in HRV alongside traditional subjective self-report measures (concussion symptoms) provides a foundation for interpreting change following concussion. The objectives were to: (1) explore the influence of age and sex on HRV; (2) examine the relationship between HRV and baseline/pre-injury concussion symptom domains (physical, cognitive, emotional, fatigue). Method: Healthy, youth athletes 13-18 years of age (N=294, female=166 [56.5%], male=128 [43.5%]) participated in this cross-sectional study. Age, sex, and concussion-like symptoms, were collected as part of a baseline/pre-injury assessment. The Post Concussion Symptom Inventory (PCSI) was used to collect domain scores for physical, cognitive, emotional and fatigue symptoms. HRV was collected for 24 hours. Outcome Measures: Time (SDNN, RMSSD, pNN50) and frequency (HF, Total Power) domain HRV measures. Variables were logarithmically transformed to increase robustness of linear regression models. Results: Older participants displayed significantly higher HRV compared to younger participants. Females displayed significantly lower HRV compared to males. A significant interaction effect between concussion-like symptoms and HRV indicated differential patterns as a function of sex. Youth athletes who reported more cognitive symptoms had lower HRV. Conclusions: HRV has the potential to be used in conjunction with subjective, self-reported symptoms, as part of post-concussion assessment. Baseline/pre-injury trends in HRV underscore the value in understanding key demographic and concussion-like factors that drive change in HRV.